Dissociative Trauma and Obsessive–Compulsive Symptoms in Primary Care: A Case Report and Home-Based Interventions - Anugrah Akbar Pambudi; Prastika Candra Triastuti; Arifah Pelangi Nusa (Universitas Pahlawan Tuanku Tambusai, 2026)
Background In Bali, 1,884 cases of mental disorders were recorded in 2024, underscoring increasing mental health demands in primary care. Comorbid dissociation and obsessive–compulsive disorder (OCD) can be difficult to detect and manage, particularly when trauma histories are present. This case report describes a trauma-informed biopsychosocial approach using feasible home-based adjuncts in a primary care setting. Case Presentation A 21-year-old female university student presented with poor concentration, intrusive negative inner voices, intrusive sexual urges, fixation on strangers, compulsive pornography use, and compulsive masturbation, accompanied by shame, social withdrawal, and sleep disturbance. She disclosed repeated childhood sexual abuse. Screening showed clinically significant dissociation (Dissociative Experiences Scale [DES] >30) and severe OCD (Yale–Brown Obsessive Compulsive Scale [Y-BOCS] 28). Psychotic disorder was considered unlikely due to preserved reality testing. Management and Outcome The patient received psychoeducation and a primary care psychiatry plan emphasizing trauma-informed, home-based strategies: mindfulness breathing, grounding techniques, and omega-3 supplementation with nutritional counseling. At week 1, she reported mild relief of intrusive voices during dissociative episodes when applying breathing and grounding exercises. By week 3, she reported fewer dissociative episodes, reduced severity of compulsive behaviors (including decreased compulsive masturbation frequency), and improved sleep quality and mood stability alongside more regular eating patterns. Conclusion This case highlights that early, trauma-informed assessment using standardized tools (DES and Y-BOCS) can support accurate recognition of dissociative–OCD presentations in primary care. A biopsychosocial approach integrating structured home-based interventions (mindfulness, grounding, and nutrition/omega-3 support) may provide practical symptom relief and functional improvement while pathways to specialist care are arranged.